Strategi Kesantunan Mata Najwa dalam episode Kami Bersama Novel - Tiani, Riris (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
Mata Najwa was the one of talkshow in Trans 7 which discuss about top topic in Indonesia. This research focuses on the direct speech which express at Mata Najwa “Kami Bersama Novel” at Trans 7. The purpose of this study is to describe and classify the form of compliance and infraction of the principle language politeness by Leech. The data source in this research are form of broadcast transcriptions which are divided into seven part which relate with research object. The research method used in this research is the method of referring with using the technique of note. The result of the study of compliance and infraction of the principle of politeness in this talkshow are eight compliance of the principle politeness, and six infraction of the principle politeness. This research found more compliance, because great image who have several figures, so it is able to be polite in conducting speeches.